THE COMMUTATIVITY OF PRIME NEAR RINGS - Ibraheem, Afrah Mohammad (International Journal of Research -GRANTHAALAYAH, 2018)
Let N be a near-ring, and σ be an automorphisms of N. An additive mapping d from a near-ring N into itself is called a reverse σ-derivation on N if d (xy) = d(y) x + σ(y) d(x), holds for all x, y∈ N. In this paper, we shall investigate the commutativity of N by a reverse σ-derivation d satisfied some properties, when N is a prime ring.